“I Am Not a Palatable Jew”: Jewish Continuity, Identity, and Inheritance Across Generations - Belfer, Dahlia (My University, 2025)
This thesis explores Jewish continuity, identity, and inheritance through intergenerational storytelling, ritual practice, and community-based research. Grounded in my own positionality as a Jewish disabled woman and granddaughter of survivors, the work asks: What does it mean to continue? How is Jewish knowledge transmitted, embodied, refused, and reimagined across generations within the context of structural antisemitism, diasporic identity, and colonial modernity? Using a braided theoretical framework that brings Jewish epistemologies into dialogue with Critical Race Theory, decolonial thought, and interpretive phenomenology, this study engages Jewish practices such as Shabbat, challah baking, and Havdalah as both cultural rituals and epistemological methods. Data was gathered through community-based research with members of my own Jewish community, where intergenerational participants shared stories, memories, and reflections on Jewish identity, grief, and continuity. Findings highlight the persistence of fragmented inheritance, the ongoing negotiation of Jewish identity within and against antisemitic structures, and the centrality of embodied ritual and relational care in sustaining cultural transmission. Themes of refusal, improvisation, and joy emerged alongside grief and loss, underscoring that Jewish continuity is not only survival but an active, creative, and insurgent practice. This thesis argues that Jewish epistemologies, embodied, dialogical, diasporic, and recursive, offer not only a means of cultural survival but also a methodological intervention for social work and allied fields. By treating memory as responsibility, ritual as theory in motion, and community as co-keeper of knowledge, the work insists that Jewish continuity matters: as love, as refusal, and as a practice of carrying forward futures that honour both rupture and regeneration.
Keywords: Jewish continuity; Jewish community; diaspora; intergenerational; embodiment; antisemitism